Metrology, Inspection, and Process Control for Microlithography XVIII 2004
DOI: 10.1117/12.535871
|View full text |Cite
|
Sign up to set email alerts
|

Time-based PEB adjustment for optimizing CD distributions

Abstract: In this paper we investigate the impact of bake plate temperature variability throughout the entire bake trajectory on resulting critical dimension. For a poorly-controlled bake plate, it is found that the correlation between the temperature profile and CD distribution is high throughout the entire bake cycle, including the steady state sector. However, for a well-controlled, multiple-zone bake plate, the correlation is only significant during the transient heating sector, since in those cases the steady state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…For current generation of photoresist, the temperature of the wafer during this thermal cycle has to be controlled to a high degree of precision both spatially and temporally. A number of recent investigations also show the importance of proper bakeplate operation on CD control Friedberg, et al [2004]. The ability to control the temperature of the wafer to different setpoint is exploited in this application.…”
Section: Real-time CD Uniformity Controlmentioning
confidence: 99%
“…For current generation of photoresist, the temperature of the wafer during this thermal cycle has to be controlled to a high degree of precision both spatially and temporally. A number of recent investigations also show the importance of proper bakeplate operation on CD control Friedberg, et al [2004]. The ability to control the temperature of the wafer to different setpoint is exploited in this application.…”
Section: Real-time CD Uniformity Controlmentioning
confidence: 99%
“…For example, Sturtevant et al [3] reported a 9% variation in the linewidth or critical dimension (CD) per 1% variation in temperature for a deep ultraviolet (DUV) resist. A number of recent investigations also show the importance of proper bakeplate operation on CD control [5,6].…”
Section: Introductionmentioning
confidence: 95%
“…Additional challenges are sure to emerge from the (as yet unmeasured and unspecified) photoresist sensitivity to the transient aspects of the PEB step, although recent experiments have shown that postdevelop CD is particularly sensitive to this component of the PEB process. 2 In this work we present the results of experiments performed using the static Microfield Exposure Tool (MET) printing system at the Advanced Light Source at Lawrence Berkeley National Laboratory. [3][4][5] This system uses synchrotron radiation at a wavelength of 13.5 nm and the optic has a numerical aperture (NA) of 0.3 and a field size of 600 µm 200 µm at the wafer.…”
Section: Introductionmentioning
confidence: 99%